Pagtatagpo - Reyes, Christi Lansang 1993- (2014)
"Pagtatagpo tells the story of Ruth, a nurse and a mother who seeks to be reconciled with her daughter. Her daughter Ammi, who had eloped, finds out that she is pregnant. When confronted with this fact, Ruth struggles even more to accept her daughter's actions and forgive her. Ruth only shares her burden with Sol, a patient she grew close to. Ruth learns about forgiveness from Sol towards the end of Sol's life. The film is about meeting expectations and meeting halfway. People sometimes fail to meet expectations. People arrive at forgiveness of another's shortcomings when they admit their own failures. Pride is antithetical to forgiveness, and forgiveness is a compromise that is needed for any relationship to last."